2013
DOI: 10.1088/0004-637x/765/2/81
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Alfvénic Waves From Corona to Chromosphere and Consequences for Solar Flares

Abstract: How do magnetohydrodynamic waves travel from the fully ionized corona, into and through the underlying partially ionized chromosphere, and what are the consequences for solar flares? To address these questions, we have developed a 2-fluid model (of plasma and neutrals) and used it to perform 1D simulations of Alfvén waves in a solar atmosphere with realistic density and temperature structure. Studies of a range of solar features (faculae, plage, penumbra and umbra) show that energy transmission from corona to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
82
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 79 publications
3
82
1
Order By: Relevance
“…Thermal radiation from soft X-rays, EUV, and UV can also contribute to this process, but this contribution was found to be very small (Allred et al 2005). Other more recent works have raised questions about the viability of this mechanism in the light of recent observations (Fletcher & Hudson 2008) and suggested Alfvén wave propagation as an alternate energy transport mechanism from the corona to chromosphere during flares (Russell & Fletcher 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thermal radiation from soft X-rays, EUV, and UV can also contribute to this process, but this contribution was found to be very small (Allred et al 2005). Other more recent works have raised questions about the viability of this mechanism in the light of recent observations (Fletcher & Hudson 2008) and suggested Alfvén wave propagation as an alternate energy transport mechanism from the corona to chromosphere during flares (Russell & Fletcher 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, if this energy were later used to accelerate chromospheric electrons (Fletcher & Hudson 2008) or to re-accelerate energetic electrons in the chromosphere that had previously precipitated from the corona (Brown et al 2009), then the electron number problem could be disposed of. Alternatively, since MHD waves are capable of transporting energy to the chromosphere and heating it by ion-neutral friction (Emslie & Sturrock 1982;Russell & Fletcher 2013), they could also contribute directly to flare radiative emissions, thus reducing the energy flux that must be provided by electron beams.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, all of which apply to the Sun, Poynting flux or waves can be the dominant form of outgoing energy flux. As discussed by Fletcher & Hudson (2008) and Russell & Fletcher (2013), the Poynting flux carried by even small amplitude MHD waves in solar active regions can be of the order required to power the radiative emissions of a flare, so it is interesting to ask the general question of what happens to the waves produced by magnetic reconnection and the energy they carry.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors, e.g. Russell & Fletcher (2013), have even suggested that MHD waves may be responsible for energy transport from the reconnection region to the flare foot-points contradicting the conventional thick-target model. Three possible mechanisms exist: the oscillations are excited by the external flare trigger, within the flare itself, or in post-flare loops (Mathioudakis et al 2003(Mathioudakis et al , 2006 E-mail: jgd@arm.ac.uk Pandey & Srivastava 2009;McLaughlin et al 2012;Srivastava, Lalitha & Pandey 2013;Pucci, Onofri & Malara 2014).…”
Section: Introductionmentioning
confidence: 99%